2016
DOI: 10.1007/s40279-016-0524-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxford and Cambridge Boat Race: Performance, Pacing and Tactics Between 1890 and 2014

Abstract: Key points:1. Oxford and Cambridge crews are now significantly faster and heavier in comparison to their racing predecessors 2. All crews in the 124 year sample displayed a fast start racing strategy 3. Obtaining an early advantage appears more meaningful than the selection of starting station despite undulations in the river course 2 Abstract:Background: Currently no studies have examined the historical performances of Oxford and Cambridge Boat Race crews in the context of performance, pacing and tactics whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…This tactic can be adopted by lower-finishing athletes to avoid a "catastrophic event" (Thiel et al, 2012), whereby the athlete would run so fast relative to ability in trying to keep up with the leaders that they would have to drop out. In events such as rowing, it is common to see differential pacing strategies according to ability in a race, where race outcome is often established as early as 25% of the total distance (Edwards et al, 2016) and ∼50% of distance in Olympic events (Garland, 2005). However, it should not be forgotten that many athletes are likely to be realistic about their prospects FIGURE 9 | The individual 1-km segment speeds for the medalists in the men's and women's 50 km racewalk events at the 2017 IAAF World Championships.…”
Section: Discussionmentioning
confidence: 99%
“…This tactic can be adopted by lower-finishing athletes to avoid a "catastrophic event" (Thiel et al, 2012), whereby the athlete would run so fast relative to ability in trying to keep up with the leaders that they would have to drop out. In events such as rowing, it is common to see differential pacing strategies according to ability in a race, where race outcome is often established as early as 25% of the total distance (Edwards et al, 2016) and ∼50% of distance in Olympic events (Garland, 2005). However, it should not be forgotten that many athletes are likely to be realistic about their prospects FIGURE 9 | The individual 1-km segment speeds for the medalists in the men's and women's 50 km racewalk events at the 2017 IAAF World Championships.…”
Section: Discussionmentioning
confidence: 99%
“…Also in the field, it was demonstrated that athlete–environment interactions affected athletic decisions and pacing behavior. Observational studies with large datasets and advanced statistics explored different competitive events involving head-to-head competition such as short track speed skating, rowing, running and cycling (Jones and Whipp, 2002 ; Paton and Hopkins, 2006 ; Dwyer et al, 2013 ; Hanley, 2013 , 2014 , 2015 ; Moffatt et al, 2014 ; Renfree et al, 2014b ; Edwards et al, 2016 ; Konings et al, 2016a ; Noorbergen et al, 2016 ). In all these studies, tactical components, such as favorable positioning, drafting, competing for the optimal line, and minimizing fall risk, seemed to influence decisions and draw athletes away from the energetically favorable strategies as would be performed in time-trial exercise.…”
Section: Does An Opponent Make a Difference At All?mentioning
confidence: 99%
“…The distribution of energy over a race (i.e. pacing) has proven to be a decisive factor in athlete performance in both time trials 1,2 and head-to-head competitions [3][4][5] . Several modelling and experimental studies have found that there is a multitude of factors that influence the pacing process, which include: the duration of the event 6 , perceived level of fatigue throughout the race 7 , previously fatiguing exercise (qualification before a final) 8 , the competitive environment 5,8 , and specific demands of a sport 9 .…”
Section: Introductionmentioning
confidence: 99%